MARKETING STRATERGY FOR ZEE NETWORK - Glenn Evorius Pattiata; Soumini Pathak (AIBPM Publisher, 2019)
Television is one of the electronic items that can be an information channel, entertainment, and also a marketing media. This television also has a vital role in people's lives to become their daily entertainment. The research aim of our research was to find solutions to the marketing of existing bank products so that products from Zee Network were more favored by customers and could outperform other television channel. Data will be collected by literature review and will be analyzed through quantitative methods. The results of this study are to market products from Zee Network so that they can be used by consumers worldwide The research conducted on the topic, “Promotion of television networks in comparison to Zee Network” is basically a promotional strategy of television networks in India. The research comprises the response obtained from a sample of viewers and a study of different factors preferred by viewers with an investigation on the reasons for the same. Here, data is obtained by secondary methods of literature review and analysis of the statistics available to the public. The study focuses on devising a strategy to promote Zee Network based on the reasons behind the comparatively lower viewership of Zee television network when compared to other in India as well as Indonesia like Jakarta. Simultaneously, it also tends to investigate on various attributes such as the viewership pattern in the region, the core competencies of each network, the opinion on the content of programs, the preference of the viewers toward the presentation styles, etc. The result ultimately suggests that it should complete some certain key factors such as customer satusfaction are also found to be influential in driving higher rating and viewership for the channels. The result of our study will be on the basis of these factors, the promotional strategy development will help Zee Network increase their viewership. Keywords: televison, entertainment, Zee Network,attributes, viewership